21-Hydroxypregnane 21-O-malonylation, a crucial step in cardenolide biosynthesis, can be achieved by substrate-promiscuous BAHD-type phenolic glucoside malonyltransferases from Arabidopsis thaliana and homolog proteins from Digitalis lanata - Tropper, Marina; Höhn, Stephanie; Wolf, Laura-Sophie; Fritsch, Julia; Kastner-Detter, Nina; Rieck, Christoph; Munkert, Jennifer; Meitinger, Nadine; Lanig, Harald; Kreis, Wolfgang (Phytochemistry, 2021)
Three putative 21-hydroxypregnane 21-O-malonyltransferases (21MaT) from Digitalis lanata were partially purified.Two of them were supposed to be BAHD-type enzymes. We were unable to purify them in quantities necessary for reliable sequencing. We identified two genes in A. thaliana coding for substrate-promiscuous BAHDtype phenolic glucoside malonyltransferases (AtPMaT1, AtPMaT2) and docked various 21-hydroxypregnanes into the substrate-binding site of a homology model built on the BAHD template 2XR7 (NtMaT1 from N. tabacum). Recombinant forms of Atpmat1 and Atpmat2 were expressed in E. coli and the recombinant enzymes characterized with regard to their substrate preferences. They were shown to malonylate various 21-hydroxypregnanes. The Atpmat1 sequence was used to identify candidate genes in Digitalis lanata (Dlmat1 to Dlmat4). Dlmat1 and Dlmat2 were also expressed in E. coli and shown to possess 21-hydroxypregnane 21-O-malonyltransferase activity.<br
Keywords: Digitalis lanata; Plantaginaceae; Foxglove; Protein purification; Protein modeling; Gene expression analysis; Cardenolides; BAHD; Pregnane 21-O-malonyltransferase